Gossip and the efficiency of interactions - Fehr, Dietmar; Sutter, Matthias (Games and economic behavior, 2019)
Human communication often involves a large amount of gossiping about others. Here we study in an experiment whether gossip affects the efficiency of human interactions in an experimental trust game. Third parties can send unverifiable messages about a trustee's behavior to a trustor. We find that this form of gossip increases trust and trustworthiness compared to a situation without a third party. However, a large part of this increase is due to the mere observation of trustees through third parties. In further control treatments we check the robustness of our findings by examining the effects of the information structure, costs or informational value of gossip.
Available online 18 October 2018
Gesehen am 25.06.2019